2016
DOI: 10.1007/s00167-016-4352-2
|View full text |Cite
|
Sign up to set email alerts
|

High mid-term revision rate after treatment of large, full-thickness cartilage lesions and OA in the patellofemoral joint using a large inlay resurfacing prosthesis: HemiCAP-Wave®

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The patient had been out of work as a carpenter for almost 2 years and was at risk of losing his ability to work completely and becoming a heavy financial burden on society. We know from other studies [6,7,8,10] -that the loss of working ability can be fatal for such patients, who are still of working age, and the economic costs for society enormous, especially for these patients in the "Treatment Gap". In the US, 3.6 million patients with symptomatic knee-pain fall into this group [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient had been out of work as a carpenter for almost 2 years and was at risk of losing his ability to work completely and becoming a heavy financial burden on society. We know from other studies [6,7,8,10] -that the loss of working ability can be fatal for such patients, who are still of working age, and the economic costs for society enormous, especially for these patients in the "Treatment Gap". In the US, 3.6 million patients with symptomatic knee-pain fall into this group [10].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of (osteo) Chondral lesions remains a clinical challenge. [1][2][3]6,7,8,16] A "gap" has been identified (9), where some patients with focal knee-lesions are considered too old for biological treatment or failed treatment, but too young for uni-or total arthroplasty (UKA/TKA). In order to fill this gap, an innovative, patient-specific metal implant (Episealer) has been designed from MRI-images and the lesion-size, and ongoing CPL (Controlled Product Launch) is taking Place, with almost 2-year follow-up.…”
Section: Objectivementioning
confidence: 99%
“…On the other hand, Laursen also showed a significant improvement in 2-year followup subjective scores, but the revision rate after 6 years was up to 28%. 20 This early failure rate seems rather unacceptable for a knee prosthesis such as the HemiCAP ® Wave prosthesis. Patel et al in another clinical trial with small number of patients (16 patients) demonstrated excellent early results with the HemiCAP ® Wave prosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…An arm with metal patches was considered, but it was decided that these were still experimental with insufficient data. A high revision rate was reported with the HemiCAP-Wave patch [ 39 ]. However, Becher and Cantillier [ 6 ] reviewed five other studies, wherein the revision rate was only about 10%.…”
Section: Discussionmentioning
confidence: 99%